Effects of Dioctyl Phthalate on Performance of Asphalt Sealant - Yang Ming Luo; Hao Yan Guo; Zhen Jun Wang; Zhuo Ran Liu (Advances in Materials Science and Engineering)
Dioctyl phthalate (DOP) was introduced into asphalt-based sealant as a plasticizer in this work. Four kinds of sealants with different DOP content were prepared, and thermal stability and low-temperature performance of five samples with asphalt as a control group were evaluated by fluidity test, softening point test, thermogravimetric-differential thermal analysis (TG-DTA), low-temperature tensile test, and differential scanning calorimeter (DSC), respectively. Furthermore, the mechanism of DOP on sealant properties was analyzed by Fourier transform infrared spectroscopy (FTIR) and fluorescence microscope. Results show that DOP can significantly improve the low-temperature performance of sealant, but slightly deteriorate the high-temperature performance. This is because DOP can supplement the light component of sealant and enhance the fluidity of the internal components. On the one hand, DOP reduces the apparent activation energy of sealant and lowers the barrier to chemical reactions, indicating that DOP is slightly detrimental to the thermal stability of sealant. On the other hand, DOP greatly reduces the glass transition temperature of sealant and improves its low-temperature performance. However, there is no evident chemical reaction between DOP and sealant, and physical effects play a major role in the effects of DOP on sealant properties. In addition, DOP can promote the expansion and cross-linking of the polymer in the sealant and ultimately enhance the compatibility between asphalt and polymer molecules. In short, DOP is recommended as a plasticizer to prepare asphalt sealants with excellent properties.